A NEW APPROACH IN APPLICATION AND DESIGN OF TOROIDAL AXIAL-FLUX PERMANENT MAGNET OPEN-SLOTTED NN TYPE (TAFPMOS-NN) MOTOR - (:unkn) unknown (UNIV OSIJEK, TECH FAC, 2015)
This paper presents a novel approach in design of toroidal axial flux permanent magnet open-slotted NN type (TAFPMOS-NN) motor. TAFPMOS-NN motor is an accomplished both theoretical and experimental model. The results of theoretical works and experimental works are performed. TAFPMOS-NN has open-slotted structure and the winding on the core surface which are the most important properties of TAFPMOS-NN motor. This situation has created the hybrid structure electric machine by combining toroidal winding without open-slotted motor properties and toroidal winding with open-slotted motor properties. The mentioned motor types have a problem such as cogging torque. The cogging problem is resolved greatly by the proposed method so that high torque, efficiency and cost saving for TAFPMOS-NN type motor are acquired.
Keywords: finite element analysis; optimization; toroidal axial flux permanent magnet open-slotted NN type motor; COGGING TORQUE; MACHINES